The role of exopolymers produced by Sphingomonas paucimobilis in biofilm formation and composition - Azeredo, Joana (2000)
Exopolymers have been associated with the initial adhesion of bacteria, which is the primary step for biofilm formation. Moreover, the polymeric matrix of biofilms has a considerable influence on some of the most important physical and physiological properties of biofilms. The role of extracellular polymers in biofilm formation was studied using three mutants of sphingomonas paucimobilis with increasing capabilities for exopolymer production. The physical, biochemical and physiological properties of three different layers oh each biofilm were determined. The layers were detached by submitting the biofilm to increasing shear stress. The results revealed that the presence of exopolymers in the growth medium was essential for biofilm formation. The mutant producing the highest amount of exopolymer formed very thick biofilms, while the biofilms formed by the medium exopolymer producer were on average 8 times thinner. The lowest exopolymer producer did not form biofilm. In both types of biofilms, exopolymer density increased with depth, although this tendency was more significant in thinner biofilms. Cell distribution was also more heterogeneous in thinner biofilms, exhibiting a greater accumulation of cells in the inner layers. The thicker biofilms had very low activity in the inner layer. This was related to a high accumulation of proteins and DNA in this layer due to cell lysis and hydrolytic activity. Activity in the thin biofilm was constant throughout its depth, suggesting that there was no nutrient limitation. The production of exopolymers by each cell was constant throughout the depth of the biofilms, although it was greater in the case of the higher producer.